1998
DOI: 10.1038/sj.gt.3300752
|View full text |Cite
|
Sign up to set email alerts
|

The effect of synthetic surfactant Exosurf on gene transfer in mouse lung in vivo

Abstract: Gene transfer in the lung holds promise for the treatment for 5 days thereafter. When DNA was delivered in a 50% of diseases such as pulmonary fibrosis, cystic fibrosis and suspension of Exosurf, the expression of either CAT or asthma. Pulmonary surfactant has been reported to Luc was significantly reduced by 89.6 ± 1.4% and enhance expression from endobronchial, adenovirus-82.7 ± 10.5%, respectively. The decrease in Luc mediated gene transfer in experimental animals. This study expression was closely correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 31 publications
(45 reference statements)
3
35
0
1
Order By: Relevance
“…The reporter plasmid pCF1CAT has been described in detail previously (14,15). Plasmid DNA was isolated from bacterial transformants by double cesium chloride gradient and endotoxin levels in each batch of plasmid was determined by limulus assay by the Vector Core Laboratory at the University of Michigan.…”
Section: Coating Of Collagen Membranes With Dendrimer-dna Complexesmentioning
confidence: 99%
“…The reporter plasmid pCF1CAT has been described in detail previously (14,15). Plasmid DNA was isolated from bacterial transformants by double cesium chloride gradient and endotoxin levels in each batch of plasmid was determined by limulus assay by the Vector Core Laboratory at the University of Michigan.…”
Section: Coating Of Collagen Membranes With Dendrimer-dna Complexesmentioning
confidence: 99%
“…Preliminary results have indicated that administration by this route may not led to optimal gene expression when compared to 'naked' DNA delivery [78]. Polymerase chain reaction (PCR) confirmed long-term plasmid DNA survival when complexed with dendrimer.…”
Section: Experimental Trialsmentioning
confidence: 96%
“…The pCF1-luciferase (pCF1-Luc) plasmid, which contains the cytomegalovirus promoter/enhancer region and firefly (Photinus pyralis) luciferase gene, was purified using an alkaline lysis procedure with the CONCERT plasmid purification system (GibcoBRL, Gaithersburg, MD, USA) according to the manufacturer's instructions [28]. The plasmid was further purified via cesium chloride ultracentrifugation.…”
Section: Plasmid Dna and Endotoxin Testingmentioning
confidence: 99%